Edukasi Pijat Bayi Kepada Ibu Dengan Balita Kelurahan Sumber, Kota Surakarta - Indiana Radinda; Umi Budi Rahayu; Seliana Sinta Debi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Baby massage is one of communication design from a person to a baby with so many benefits for the baby that receive baby massage. Sadly, the knowledge about baby massage in this community is not enough. Education about baby massage was given for a mother with 1 – 36 months old toddler that usually checking their child at RW 14 Kelurahan Sumber, Surakarta City, that aim to increase the knowledge about the definition to how to do baby massage. The education given by oral presentation and leaflet, and also a demo on how to do a baby massage. Leaflet that contains the theory given to audiences so the education can be applicated based on the instructions. Pretest and Posttest was given and contain some simple questions with “Yes/No” answers includes the knowledge of effects, contraindication, and procedure of baby massage and how of then their baby receive it. Pretest was given before the education and it results the knowledge of baby massage in mother with toddler were just about 30% and it increased after the education for 70% with similar questions after the education so it canbe conclude that publicly, especially people that usually checking their children, knows how to do baby massage.